Multidisciplinary Approach to Patients With Metastatic Spinal Cord Compression: A Diagnostic Therapeutic Algorithm to Improve the Neurological Outcome - Rispoli, Rossella; Reverberi, Chiara; Targato, Giada; D’Agostini, Serena; Fasola, Gianpiero; Trovò, Marco; Calci, Mario; Fanin, Renato; Cappelletto, Barbara (Frontiers in Oncology, 2022)
Introduction The morbidity associated with metastatic spinal disease is significant because of spinal cord and/or nerve root compression. The purpose of this paper is to define a diagnostic-therapeutic path for patients with vertebral metastases and from this path to build an algorithm to reduce the devastating consequences of spinal cord compression. Materials and Methods The algorithm is born from the experience of a primary care center. A spine surgeon, an emergency room (ER) physician, a neuroradiologist, a radiation oncologist, and an oncologist form the multidisciplinary team. The ER physician or the oncologist intercept the patient with symptoms and signs of a metastatic spinal cord compression. Once the suspicion is confirmed, the following steps of the flow-chart must be triggered. The spine surgeon takes charge of the patient and, on the base of the anamnestic data and neurological examination, defines the appropriate timing for magnetic resonance imaging (MRI) in collaboration with the neuroradiologist. From the MRI outcome, the spine surgeon and the radiation oncologist consult each other to define further therapeutic alternatives. If indicated, surgical treatment should precede radiation therapy. The oncologist gets involved after surgery for systemic therapy. Results In 2021, the Spine and Spinal Cord Surgery department evaluated 257 patients with vertebral metastasis. Fifty-three patients presented with actual or incipient spinal cord compression. Among these, 27 were admitted due to rapid progression of symptoms, neurological deficits and/or spine instability signs. The level was thoracic in 21 cases, lumbar in 4 cases, cervical in 1 case, sacral in 1 case. Fifteen were operated on, 10 of these programmed and 5 in emergency. Discussion Patients with a history of malignancy can present to the ER or to the oncology department with symptoms that must be correctly framed in the context of a metastatic involvement. Even when there is no previous cancer history, the patient’s pain characteristics and clinical signs must be interpreted to yield the correct diagnosis of vertebral metastasis with incipient or current spinal cord compression. The awareness of the alert symptoms and the application of an integrated paradigm consent to frame the patients with spinal cord compression, obtaining the benefits of a homogeneous step-by-step diagnostic and therapeutic path. Early surgical or radiation therapy treatment gives the best hope for preventing the worsening, or even improving, the deficits. Conclusions Metastatic spinal cord compression can cause neurological deficits compromising quality of life. Treatment strategies should be planned comprehensively. A multidisciplinary approach and the application of the proposed algorithm is of paramount importance to optimize the outcomes of these patients.